2019
DOI: 10.1007/s00210-019-01749-5
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor CG200745 ameliorates high-fat diet-induced hypertension via inhibition of angiotensin II production

Abstract: Obesity is growing rapidly worldwide due to consumption of westernized diet and lack of exercise. Obesity is one of the major risk factors of hypertension. The novel histone deacetylase (HDAC) inhibitor CG200745 was originally developed to treat various cancers. Previous studies showed that CG200745 attenuated hypertension through inhibition of cardiac hypertrophy and fibrosis in deoxycorticosterone acetate-induced hypertensive rat. The purpose of this study is to investigate the role and underlying mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Yoon et al. showed Class I HDACi-treated hypertension in an obesity murine model via inhibition of angiotensin II ( 46 ). However, in our model, there was no significant difference in plasma renin levels at the 12-month time point, indicating that the renin-angiotensin-aldosterone system was not driving the hypertension in the AKI cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al. showed Class I HDACi-treated hypertension in an obesity murine model via inhibition of angiotensin II ( 46 ). However, in our model, there was no significant difference in plasma renin levels at the 12-month time point, indicating that the renin-angiotensin-aldosterone system was not driving the hypertension in the AKI cohort.…”
Section: Discussionmentioning
confidence: 99%
“…This finding has prompted interest in SIRT1 as a potential pharmacological target for obesity and obesity-related diseases [ 173 , 175 ]. Recent studies in mouse models of obesity have already demonstrated that HDAC inhibitors stimulate adipose tissue function and oxidative potential, improving the metabolic profile [ 176 , 177 , 178 ]. Additionally, epigenetic changes upon PPARγ-ligand binding have been studied in relation to their effects on adipogenesis.…”
Section: The Pparα and Pparγ Epigenetic Landscape In Diseasementioning
confidence: 99%
“…Various studies have shown that histone deacetylase (HDAC) inhibitors are effective in the treatment of cancer, autoimmune diseases, inflammatory diseases, interstitial fibrosis, cardiovascular diseases, and renal diseases [7,8]. Our previous studies reported that valproic acid has cardiac and vascular protective effects [2] and mocetinostat attenuates aortic remodelling [9] in pressure overload-induced cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Trichostatin A, valproic acid, and SK-7041 prevent hypertrophy of the heart in animal models of angiotensin II-infused cardiac hypertrophy [13]. Valproic acid ameliorates the angiotensinogen II production in the kidney in high-fat diet-induced HTN model [7]. Trichostatin A [14] and CG200745 [15] attenuate renal fibrosis in unilateral ureteral obstruction mouse model.…”
Section: Introductionmentioning
confidence: 99%